Police public order and civil liberties - "McCabe, Sarah" (London, 1988)
This report describes the policing of the 1984-5 miners' strike in detail, examining the role of the police and why they found themselves playing a part in the defeat of the strike. Both the events of 1984-5 and the longer-term issues are examined.
Keywords: Great Britain - coal industries - miners - industrial re